PATTERN AND CHARACTERISTICS OF DRUSEN SUBTYPES IN CHINESE AND INDIAN POPULATIONS IN SINGAPORE. Issue 2 (February 2023) - Takahashi, Kengo; Song, Youngseok; Cheong, Kai Xiong; Fenner, Beau J.; Teo, Kelvin Yi Chong; Chee, Miao Li; Li, Hengtong; Tham, Yih-Chung; Cheung, Chui Ming Gemmy; Cheng, Ching-Yu; Wong, Tien Yin; Yanagi, Yasuo; et al.
Abstract : Supplemental Digital Content is Available in the Text. This study summarized the pattern and characteristics of drusen subtypes in East and South Asian populations. The systemic parameters, choroidal thickness, and volume are compared among eyes with pachydrusen, hard drusen, soft drusen, and without drusen. The drusen distribution was additionally compared. Abstract : Purpose: To report the pattern and characteristics of drusen subtypes in Asian populations and the association with choroidal thickness. Methods: This is the cross-sectional analysis of the population-based cohort study. Two thousand three hundred and fifty-three eyes of 1, 336 Chinese and Indian participants aged older than 50 years, eyes with best-corrected visual acuity better than 20/60, and without other retinal diseases were recruited. Pachydrusen, reticular pseudodrusen, soft and hard drusen were graded on both color fundus photographs, and optical coherence tomography imaging with automated segmentation yielding and measurements of choroidal thickness. Results: Nine hundred and fifty-five Chinese and 381 Indians were included in the final analysis. The pattern of pachydrusen, soft drusen, hard drusen, and reticular pseudodrusen was 14.0%, 3.7%, 12.5%, and 0.2%, respectively. Mean choroidal thickness was the thickest in eyes with pachydrusen (298.3 μ m; 95% confidence interval: 290.5–306.1), then eyes with hard (298.1 μ m; 95% confidence interval: 290.6–305.5) and soft drusen (293.7 μ m; 95% confidence interval: 281.9–305.4) and thinnest in eyes without drusen (284.6 μ m; 95% confidence interval: 280.5–288.7). Systemic associations of the various drusen subtypes also differed. Conclusion: Patterns, characterization and choroidal thickness of drusen subtypes, and their associations provide insights into the Asian phenotypic spectrum of age-related macular degeneration and the underlying pathogenesis.